Runtime analysis of area-efficient uniform RO-PUF for uniqueness and reliability balancing - Zulfikar, Zulfikar (MDPI, 2021)
The main issue of ring oscillator physical unclonable functions (RO-PUF) is the existence of unstable ROs in response to environmental variations. The RO pairs with close frequency differences tend to contribute bit flips, reducing the reliability. Research on improving reliability has been carried out over the years. However, it has led to other issues, such as decreasing the uniqueness and increasing the area utilized. Therefore, this paper proposes a uniform RO-PUF, requiring a smaller area than a conventional design, aiming to balance reliability and uniqueness. We analyzed RO runtimes to increase reliability. In general, our method (uniqueness = 47.48%, reliability = 99.16%) performs better than previously proposed methods for a similar platform (Altera), and the reliability is as good as the latest methods using the same IC technology (28 nm). Moreover, the reliability is higher than that of RO-PUF with challenge and response pair (CRP) enhancements. The evaluation was performed in longer runtimes, where the pulses produced by ROs exceeded the counter capacity. This work recommends choosing ranges of the runtime of RO for better performance. For the 11-stage ROs, the range should be 1.598-4.30 ms, or 6.12-8.61 ms, or 12.24-12.91 ms. Meanwhile, for the 20-stage, the range should be 2.717-8.37 ms, or 10.97-16.74 ms, or 21.93-25.10 ms.